Physical and mechanical properties of Guadua lynnclarkiae, Guadua weberbaueri and Guadua superba in Ucayali, Peru - Rodríguez-Sotelo, Jefferson Alexander; Abanto-Rodriguez, Carlos; Flores-Romayna, María Angelica; Rodriguez-Vasquez, Kevin Isaac; Castillo-Torres, Dennis del; Guerra-Arévalo, Wilson Francisco; García-Soria, Diego Gonzalo; Guerra-Arévalo, Héctor; Revilla-Chávez, Jorge Manuel (Ciência Florestal, 2023)
The objective was to determine the physical and mechanical properties of Guadua lynnclarkiae, Guadua weberbaueri and Guadua superba. Three culms were collected from each species, later they were sectioned into three levels: stump (S), base (B) and over base (O). The experiment was conducted in a completely randomized design (DCA) in a factorial scheme (3E x 3N), being factor E: bamboo species with three levels: a) Guadua lynnclarkiae, b) Guadua weberbaueri and c) Guadua superba; and the N factor: culm level with three sections a) stump, b) base and c) over base, all distributed in three repetitions and 4 test tubes for physical properties. For the mechanical properties, the same experimental design and number of repetitions were used, however, 5 test tubes were used per experimental plot. Thus, the greatest contraction of the culm wall was 23.0% in Guadua lynnclarkiae at the base level. The basic density in the three species was 0.71 g cm-3. In bending, the highest modulus of rupture was recorded in Guadua superba in stump, base and over base with 55.15; 84.49 and 73.97 MPa, respectively. In parallel compression, the MoE and MoR were 11454.35 MPa and 39.50 MPa in the three species and levels. Therefore, Guadua lynnclarkiae and Guadua weberbaueri have adequate physical and mechanical properties for different uses, including civil construction. However, in Guadua superba it is recommended to carry out subsequent studies of rigidity and resistance for its use in the construction of houses in rural and urban areas.